An automated and high‐throughput method for adenosine triphosphate quantification. Issue 6 (1st December 2020) - Secka, Fatou; Allward, Nicole E.; Stoddart, Amina K.; Gagnon, Graham A.
Abstract: Exposure to microbial contamination through drinking water is a major global health concern. Effective management of microbial drinking water quality requires rapid detection equipment. Currently, microbial quality is monitored using time‐consuming laboratory methods, which delay any response. This study demonstrates the development of an automated and high‐throughput method for the measurement of viable biomass in water through the quantification of cellular adenosine triphosphate (ATP). The developed method was able to efficiently and accurately quantify cellular ATP in multiple water samples simultaneously. In addition, it proved to be 5× faster and as accurate as the Standard Test Method for Adenosine Triphosphate (ATP) Content of Microorganisms in Water (ASTM D4012). The developed method has the potential to represent a significant advancement for microbial monitoring and could benefit utilities interested in measuring viable biomass in water to monitor the health of biofilters and the effectiveness of disinfection strategies.